1991
DOI: 10.1227/00006123-199108000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Decompression in Cervical Spine Trauma: Does the Timing of Surgery Affect the Outcome?

Abstract: To clarify the ideal timing of anterior decompression and stabilization for all patients with cervical spine trauma as well as its efficacy for patients with complete deficits, we reviewed the records of 103 consecutive patients with cervical spine trauma (50 incomplete deficits, Group A; 53 complete deficits, Group B) who underwent this procedure during a 5-year period at the Shock Trauma Center. We subdivided each group according to time of surgery: early and delayed (<24 and >24 hours past inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(68 citation statements)
references
References 0 publications
3
64
0
1
Order By: Relevance
“…In the retrospective studies of Wagner and Chehrazi 33 and Levi et al, 21 comparing early-and late-treated patients, there were no differences in neurologic recovery. Even in more recent studies, based on prospective series, such as that of Duh et al, 41 39 based on a prospective randomized series, stated no difference between early and late surgery.…”
Section: Literature Reviewmentioning
confidence: 90%
See 2 more Smart Citations
“…In the retrospective studies of Wagner and Chehrazi 33 and Levi et al, 21 comparing early-and late-treated patients, there were no differences in neurologic recovery. Even in more recent studies, based on prospective series, such as that of Duh et al, 41 39 based on a prospective randomized series, stated no difference between early and late surgery.…”
Section: Literature Reviewmentioning
confidence: 90%
“…In fact, although experimental studies demonstrated that early relief of decompression improves neurological outcome in animal models, as first shown convincingly by Tarlov and Klinger 19,20 in dogs and later by Brodkey et al 46 in cats, the results of several clinical studies failed to show that patients treated early made improved recovery compared with those undergoing late surgery. 21,33,39,51 Figure 3 Analysis of homogeneity of pooled studies. Selected studies had been pooled on the basis of treatment and neurological status at admittance: early-treated patients with complete (a) and incomplete neurological deficit (b); latetreated patients with complete (c) and incomplete neurological deficit (d); conservatively managed patients with complete (e) and incomplete neurological deficit (f).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute spinal surgery, within the first 24 h following SCI, to alleviate mechanical shearing and compression forces is used to restrict primary damage to the cord, as well as secondary damage that can result from extended periods of compression [13]. In addition to spinal cord stabilization, arterial oxygenation and maintenance of mean arterial blood pressure between 85 and 90 mm Hg following acute SCI is vital in reducing secondary damage due to ischemia and hypoxia, and improving functional outcome [11,[14][15][16][17][18]. Hypothermia is also currently in clinical testing as a means of limiting secondary damage immediately following injury [19,20].…”
Section: Clinical Treatmentmentioning
confidence: 99%
“…One systematic review, considered class 2 evidence, concluded that early surgery (<24 h) results in better neurological outcome than delayed surgery (>24 h) for patients with incomplete injuries [36]. In studies of lower methodological quality, surgery prior to 24 h has also been shown to improve neurological outcomes and to reduce complications, as well as certain measures of resource use, such as overall length of hospital stay and length of intensive care unit stay [37][38][39]. Conversely, studies of similar low methodological quality, using the same time cutoff, have failed to demonstrate a positive effect with respect to neurologic outcome [40,41].…”
Section: Clinical Evidence For Surgical Decompressionmentioning
confidence: 99%